2016
DOI: 10.1038/nn.4339
|View full text |Cite
|
Sign up to set email alerts
|

Multilaminar networks of cortical neurons integrate common inputs from sensory thalamus

Abstract: Neurons in the thalamorecipient layers of sensory cortices integrate thalamic and recurrent cortical input. Cortical neurons form fine-scale, functionally cotuned networks, but whether interconnected cortical neurons within a column process common thalamocortical inputs is unknown. We tested how local and thalamocortical connectivity relate to each other by analyzing cofluctuations of evoked responses in cortical neurons after photostimulation of thalamocortical axons. We found that connected pairs of pyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 49 publications
2
81
0
Order By: Relevance
“…Combining this method with laser photostimulation of remote slice loci, in rat V1, it was possible to show that pairs of connected pyramidal cells in layer 2/3 had a greater probability of receiving joint input from any given stimulation site in layer 4, and/or from nearby sites in layer 2/3, compared to unconnected pairs (Yoshimura et al, 2005). In a similar vein (and as discussed in Figure 4B ) geniculate afferents are also more likely to co-terminate on connected pairs of pyramidal neurons in layers 4 and 3 (Morgenstern et al, 2016). Together these studies imply the existence of separate, mutually exclusive translaminar networks, although they are blind toward the featural specificity of any such network.…”
Section: Recurrent Processing Within the Forward Pathwaymentioning
confidence: 65%
See 2 more Smart Citations
“…Combining this method with laser photostimulation of remote slice loci, in rat V1, it was possible to show that pairs of connected pyramidal cells in layer 2/3 had a greater probability of receiving joint input from any given stimulation site in layer 4, and/or from nearby sites in layer 2/3, compared to unconnected pairs (Yoshimura et al, 2005). In a similar vein (and as discussed in Figure 4B ) geniculate afferents are also more likely to co-terminate on connected pairs of pyramidal neurons in layers 4 and 3 (Morgenstern et al, 2016). Together these studies imply the existence of separate, mutually exclusive translaminar networks, although they are blind toward the featural specificity of any such network.…”
Section: Recurrent Processing Within the Forward Pathwaymentioning
confidence: 65%
“…Each form of linear summation of prediction error signals, here from the LGN (refer to Section 9) is germane to the synthesis of an expectation unit, consistent with the prevalence of simple oriented receptive fields in layer 4 of mouse V1 (Niell and Stryker, 2008). Terminal arborisations of single geniculate axons favor contacts with connected excitatory neuron pairs in layers 4 and 3: this is true for presynaptic/postsynaptic pairs in L4/L4 and L4/L3, but not L3/L3; L3/L4 connected pairs are absent (Morgenstern et al, 2016). The modified gPC template shown here interprets the L4/L4 pair receiving joint input as communicating expectation units, and the L4/L3 pair as an input error unit connecting to an expectation unit.…”
Section: The Forward Pathway Through Layer 4 and Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that cortical networks are more structured than simple Erdős-Rényi networks (e.g., [4853]). One feature of cortical networks is a broad spread of neurons’ in- and out-degree distributions (i.e., the distributions of the number of synaptic inputs that each neuron receives or sends); another is broadly spread synaptic weights.…”
Section: Resultsmentioning
confidence: 99%
“…This provided a measure of both the strength and location of monosynaptic CC inputs. We then compared the strength of monosynaptic FF or FB inputs in defined dendritic compartments in pairs of neurons projecting to different areas ( Figure 2E-G) 16,17,24,25 .…”
Section: Mapping the Cell-type Specificity Of CC Connectionsmentioning
confidence: 99%